Geological Study of Chatara–Barahakshetra Section, Sunsari-Udayapur District, Eastern Nepal - Adhikari, Drona; Shrestha, Keshav; Adhikari, Purushottam; Paudayal, Khum N.; Paudel, Lalu (Bulletin of the Department of Geology, 2018)
Geological mapping was carried out in the Chatara–Barahakshetra area of east Nepal. The Siwalik of the Chatara–Barahakshetra area is divided into the Lower Siwalik and the Middle Siwalik. Each unit is further subdivided into lower and upper members. The Central Churia Thrust is overturned in the study area. Highly deformed Siwalik contain several outcrop-scale as well as a large-scale folds. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 49-58